Northern Hemisphere biome changes (> 30 degrees N) since 40 cal ka BP and their driving factors inferred from model-data comparisons - Cao, Xianyong (Dr.); Tian, Fang (Dr.); Dallmeyer, Anne; Herzschuh, Ulrike (Prof. Dr.) (Quaternary Science Reviews, 2019)
Ongoing and past biome transitions are generally assigned to climate and atmospheric changes (e.g. temperature, precipitation, CO2), but the major regional factors or factor combinations that drive vegetation change often remain unknown. Modelling studies applying ensemble runs can help to partition the effects of the different drivers. Such studies require careful validation with observational data. In this study, fossil pollen records from 741 sites in Europe, 728 sites in North America, and 418 sites in Asia (extracted from terrestrial archives including lake sediments) are used to reconstruct biomes at selected time slices between 40 cal ka BP (calibrated thousand years before present) and today. These results are used to validate Northern Hemisphere biome distributions (>30 degrees N) simulated by the biome model BIOME4 that has been forced with climate data simulated by a General Circulation model. Quantitative comparisons between pollen- and model-based results show a generally good fit at a broad spatial scale. Mismatches occur in central-arid Asia with a broader extent of grassland throughout the last 40 ka (likely due to the over-representation of Artemisia and Chenopodiaceae pollen) and in Europe with over-estimation of tundra at 0 cal ka BP (likely due to human impacts to some extent). Sensitivity analysis reveals that broad-scale biome changes follow the global signal of major postglacial temperature change, although the climatic variables vary in their regional and temporal importance. Temperature is the dominant variable in Europe and other rather maritime areas for biome changes between 21 and 14 ka, while precipitation is highly important in the arid inland regions of Asia and North America. The ecophysiological effect of changes in the atmospheric CO2-concentration has the highest impact during this transition than in other intervals. With respect to modern vegetation in the course of global warming, our findings imply that vegetation change in the Northern Hemisphere may be strongly limited ...